Unsettling Settler Food Movements: Food Sovereignty and Decolonization in Canada - Matties, Zoe (Cuizine)

(untitled) (McGill University Library, 2016)
This article examines the connections between agriculture, alternative food movements, and settler colonialism. In particular I examine how settler agriculture and control of food throughout the nineteenth and twentieth centuries has been used as a tool of colonization, and how food sovereignty offers a corrective to the imposition of Western, colonial, gendered, and racialized foodways. I also explore Indigenous food sovereignty in North America as a model that honors and reclaims Indigenous foodways and self-determination, and addresses the alarming rates of food insecurity and diet-related health issues among Indigenous populations. Following in the footsteps of feminist and decolonial scholars, I seek to critically analyse the discourses of alternative food movements to discover how alternative food movements can transform the colonial system rather than unconsciously perpetuate it. I argue that as settlers working to create equitable and sustainable food systems we must recognize complicity in colonialism, engage Indigenous perspectives and narratives, and work to support Indigenous communities seeking Indigenous food sovereignty and self-determination. To do so requires creating alliances based on learning about our differences from and with each other, and embracing settler discomfort as a motivation for change.